2016
DOI: 10.1073/pnas.1525030113
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of prediction errors for auditory events in human temporal and frontal cortex

Abstract: Predictive coding theories posit that neural networks learn statistical regularities in the environment for comparison with actual outcomes, signaling a prediction error (PE) when sensory deviation occurs. PE studies in audition have capitalized on low-frequency event-related potentials (LF-ERPs), such as the mismatch negativity. However, local cortical activity is well-indexed by higher-frequency bands [high-γ band (Hγ): 80-150 Hz]. We compared patterns of human Hγ and LF-ERPs in deviance detection using elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
160
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(183 citation statements)
references
References 46 publications
(57 reference statements)
13
160
4
Order By: Relevance
“…If gamma‐band oscillations represent the output of error units, unpredictable deviants would be expected to provoke strong gamma‐band activity, while predictable deviants should elicit a more muted response. Although Durschmid et al 182 . did find that high‐gamma (>60 Hz) responses differentiated between unpredictable and predictable deviant tones at frontal sites, unpredictable and predictable deviants elicited equivalent high‐gamma activity over temporal cortex.…”
Section: Hypothesis 3: Each Level Of the Cortical Hierarchy Houses Twmentioning
confidence: 85%
See 1 more Smart Citation
“…If gamma‐band oscillations represent the output of error units, unpredictable deviants would be expected to provoke strong gamma‐band activity, while predictable deviants should elicit a more muted response. Although Durschmid et al 182 . did find that high‐gamma (>60 Hz) responses differentiated between unpredictable and predictable deviant tones at frontal sites, unpredictable and predictable deviants elicited equivalent high‐gamma activity over temporal cortex.…”
Section: Hypothesis 3: Each Level Of the Cortical Hierarchy Houses Twmentioning
confidence: 85%
“…Accordingly, early responses to local deviants are typically confined to primary sensory cortex, while violations of complex regularities evoke activity across distributed, higher‐level areas (e.g., Ref. 182; see Ref. 42 for a review).…”
Section: Hypothesis 4: Prediction Error Minimization Is Achieved By Amentioning
confidence: 99%
“…Although little difference was seen between the mismatch response of the frontal lobe and that of STG for “predictable” stimuli, significantly stronger response of the frontal lobe was detected for “unpredictable” stimuli. That result showed that the frontal lobe was responsible for detecting “prediction errors” (Durschmid et al, ). In our study, although frontal MMR was observed in four of the 10 subjects, neither a consistent localization pattern nor association with MMR was evident in the frontal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a human intracranial study measuring high frequency neural activity demonstrated that the PFC only became active when unpredicted deviants were detected (Figure 1A, [31]). Neither predicted deviants nor standards elicited any meaningful PFC activation, while sensory areas did not distinguish between predicted and unpredicted deviants.…”
Section: Oscillatory Mechanisms Guiding Behavior and Cognitionmentioning
confidence: 99%
“…Furthermore, different frequency bands allow multiplexing different computations on several temporal scales. The graphs in a and c are reproduced with permission from [31,33]. The graphs in d and e appeared under the Creative Commons Attribution (CC BY) license [28,38].…”
Section: Figurementioning
confidence: 99%